Jabatan Gerejawi Dalam Teologi Martin Luther: Suatu Studi Teologis Terhadap Posisi Pelayan Gereja - Sirait, Musa Aprindo; Sitanggang, Pintor Marihot (Jurnal Teologi dan Pelayanan Kerusso, 2025)
This article examines Martin Luther's views on ecclesiastical office, focusing on the doctrine of the priesthood of all believers and its implications for church ministry structures. According to Luther, every believer has direct access to God without hierarchical mediation, as outlined in the doctrine of the priesthood of all believers. The study employs a theological-normative approach and a literature review of Martin Luther's works, as well as relevant biblical texts concerning ecclesiastical office. Through a theological approach and biblical analysis, this article explores the relevance of Luther's views on ecclesiastical office in the context of contemporary church ministry. The findings indicate that, according to Luther, ecclesiastical office is not a form of hierarchical domination but a ministry grounded in the Word and love. This study contributes to the contemporary church's understanding of balancing spiritual authority with pastoral responsibility. Thus, this article offers a contribution to the modern church in reformulating the understanding of ecclesiastical office in a more theological and egalitarian manner.